Percutaneous distal venous arterialisation (pDVA) in a patient with no-option chronic limb threatening ischaemia (CLTI). - Raouf, Zachariah M; Chetan, Madhurima R; Patel, Rafiuddin; Mackinnon, Tina; MacDonald, Andrew; Wigham, Andrew; Uberoi, Raman; Howard, Dominic PJ (Journal of the Nuffield Department of Surgical Sciences, 2023)
Introduction This case study presents the management and follow-up of a patient with chronic limb ischaemia (CLI). Owing to the lack of viable treatment options available, the patient elected to undergo distal venous arterialisation (DVA) as an experimental procedure to restore perfusion to his compromised limb. Methods (History and Management) 80-year-old male presenting with CLI of the left leg on a background of right below-kneeamputation, diabetes, COPD, atrial fibrillation, and antiphospholipid syndrome. Investigations revealed distal vascular disease of the left leg, poor flow into the foot with no named arteries patent identified on pre-treatment angiogram. Patient was consented for DVA as progressive necrosis of the toes had occurred despite medical management with vasodilators and attempted endovascular procedures. A fistula tract was created endovascularly between the posterior tibial artery and vein with covering stents placed across the fistula. Proximal valves of the vein were rendered incompetent with balloon venoplasty. Competing collateral veins were then occluded with covered stents two weeks post procedure due to outflow shunting identified on angiogram. Results (Outcomes) Angiogram identified good flow around the plantar arch post procedure. Examination two months post-DVA showed marked improvement with granulation tissue at wounds. Midfoot was found to be warm and perfused with good doppler signal from the arterialized vein. Healing continued at 6- month follow up with the wound deemed fully healed 1-year post procedure. Conclusions DVA represents a novel procedure for patients with no-option CLI with a patent/stump tibial artery and adjacent vein. Case based evidence suggests that using standard endovascular techniques and equipment DVA can potentially avoid major amputation. Future studies to compare outcomes of DVA in CLI patients vs controls will be needed to evaluate the effectiveness of endovascular DV